1967
DOI: 10.1021/jf60151a009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hop varieties by gas chromatographic analysis of their essential oils. Constancy of oil composition under various environmental influences

Abstract: The essential oil of several varieties of hops displayed good varietal uniformity of composition under the following environmental conditions: annual climatic conditions, climates and soils of widely different growing areas within the United States, abnormal ranges of nitrogen and phosphorus fertility over various moisture levels, development of the plant over a 4-year period (hops are perennial), maturity of the crop over a 21-day harvest period, while hosting any of several viruses, through processing, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…Particular essential oil profiles have historically been targeted in the genetic improvement of hop [97,98]. While it has long been understood that hop essential oil profiles have a genetic basis [99-102], the genetic control of total essential oil content has not been previously established in hop. QTL have been previously identified for only two individual essential oil components, caryophyllene and farnesene [14], but not for total essential oil content.…”
Section: Discussionmentioning
confidence: 99%
“…Particular essential oil profiles have historically been targeted in the genetic improvement of hop [97,98]. While it has long been understood that hop essential oil profiles have a genetic basis [99-102], the genetic control of total essential oil content has not been previously established in hop. QTL have been previously identified for only two individual essential oil components, caryophyllene and farnesene [14], but not for total essential oil content.…”
Section: Discussionmentioning
confidence: 99%
“…In the late 1950s, Howard and Slater recognized that, independent of the country in which the hops were grown, there was a varietal uniformity in the general pattern observed in the composition of the hydrocarbon fraction. A decade later, Likens and Nickerson and Buttery and Ling confirmed that the essential oil of several hop varieties displayed good varietal uniformity in their chemical composition. Likens and Nickerson established that certain components or ratios of components in the hop oil are highly specific for the individual varieties.…”
Section: Hop Essential Oilsmentioning
confidence: 95%
“…It has been established that the hop essential oil profile depends on the hop variety. In particular, the amounts of hydrocarbons and oxygenated compounds vary according to the hop variety and age . In the late 1950s, Howard and Slater recognized that, independent of the country in which the hops were grown, there was a varietal uniformity in the general pattern observed in the composition of the hydrocarbon fraction.…”
Section: Hop Essential Oilsmentioning
confidence: 99%
“…Simultaneous steam distillation-extraction in Figure 2, was conducted using a modified Likens-Nickerson apparatus (16). The apparatus consisted of the sample flask (right) where approximately 150g of dried mushrooms from China were added and mechanically stirred with 2.5L of distilled water.…”
Section: Extraction Techniquesmentioning
confidence: 99%